Personal protective equipment (PPE) use and its relation to accidents among construction workers - Sehsah, Radwa; El-Gilany, Abdel-Hady; Ibrahim, Ateya Megahed (La Medicina del Lavoro, 2020)
Background: The construction industry is characterized by a high prevalence of accidents and injuries. Inadequate risk management measures, including failure to use or incorrect use of personal protective equipment (PPE) may significantly increase the risk of accidents. Objectives: The main objectives of the current study were to measure the prevalence of PPE use and accidents and their associated factors among construction workers. Methods: A cross-sectional field study with an analytic component was carried out on 384 workers from different sites in Port-Said, Egypt, using an interview administered questionnaire. The questionnaire included sociodemographic and occupational data, practice of PPE use and accident analysis. Results: About 60% of workers use PPE during work. Main reasons for non-use are discomfort, lack of knowledge on how to use it and poor fit. Occupational accidents in the last 12 months were reported by 64.3% of workers. The main accident types were: being hit by falling objects, falls from height, and tool related accidents. Safety training was the significant independent predictor of PPE use (AOR=2.0). However, age, marital status, smoking, safety training, and PPE use were also significant independent predictors of accidents (AOR=2.4, 3.1, 0.5, 0.5, and 0.2; respectively). Discussion: Among construction workers, PPE utilization is low with significant relation to safety training while occupational accidents are common and significantly related to safety training and PPE use. Therefore, safety training should be provided, and PPE use should be enforced at construction sites.